Fe-doped hollow PtBi nanocages loaded on Bi2O2CO3-NC composite support with excellent methanol electrooxidation performance. (December 2022) - Li, W.; Gan, M.; Ma, L.; Zhao, W.; Zhan, W.; Deng, S.; Xie, F.
Abstract: A highly active and stable anode catalyst for direct methanol fuel cells is critical to commercialization. Therefore, we have synthesized a unique Fe-doped catalyst Fe–PtBi2 /Bi2 O2 CO3 -NC through the classical hydrothermal method and sodium borohydride reduction. Physical characterizations confirm the existence of Bi2 O2 CO3 nanosheets and successful loading of PtBi nanocages. It is the alternating layer arrangement of Bi2 O2 CO3, the bifunctional mechanism of PtBi alloy and the synergistic effect of each component that make the synthesized Fe–PtBi2 /Bi2 O2 CO3 -NC possess such remarkable methanol oxidation reaction activity (a mass activity of 9345 mA/mgPt in alkaline electrolyte). Moreover, electrochemical measurements also indicate that 51.7% of the mass activity was retained after 1 h durable operation, which is approximately 4.1 times than that of commercial Pt black. Fe–PtBi2 /Bi2 O2 CO3 -NC may be applied as a promising alkaline anode catalyst for direct methanol fuel cells due to its outstanding structure and performance. The specific work provides a reference for designing reliable structures and selection of doping elements to enhance the sluggish kinetics of methanol electrooxidation. Graphical abstract: Image 1 Highlights: PtBi nanocages and Bi2 O2 CO3 -NC composite support have been successfully synthesized. Hollow PtBi nanocages provide more active sites for methanol electrooxidation. The synergistic effect of each component enhances the methanol oxidation kinetics. Fe–PtBi2 /Bi2 O2 CO3 -NC exhibits excellent activity and durability in alkaline electrolyte.